2023
DOI: 10.3389/fneur.2023.1134827
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic diet for super-refractory status epilepticus (SRSE) with NORSE and FIRES: Single tertiary center experience and literature data

Abstract: Background and purposeKetogenic diet (KD) is an emerging treatment option for super-refractory status epilepticus (SRSE). We evaluated the effectiveness of KD in patients presenting SRSE including NORSE (and its subcategory FIRES).MethodsA retrospective review of the medical records was performed at the Necker Enfants Malades Hospital. All children with SRSE in whom KD was started during the last 10 years were included. A systematic search was carried out for all study designs, including at least one patient o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…Thus, patients with unexplained new onset seizures such as new onset refractory status epilepticus (NORSE) with generalized ictal EEG findings and diffuse or normal imaging findings could still benefit from these approaches. However, our logistic regression models revealed that new-onset seizures were associated with worse outcomes; thus, clinical decision-making should still be made on a case-by-case basis given the lack of high-quality evidence guiding therapy in these patients, as well as the documented role of therapies such as the ketogenic diet and immunotherapy ( 31 , 32 ). Some authors suggest the use of non-invasive neuromodulation techniques such as and transcranial magnetic stimulation (TMS) and electroconvulsive therapy (ECT) in the first week of SRSE, and consideration of neuromodulation techniques such as VNS, DBS and RNS after 2 weeks of therapy ( 33 ).…”
Section: Discussionmentioning
confidence: 93%
“…Thus, patients with unexplained new onset seizures such as new onset refractory status epilepticus (NORSE) with generalized ictal EEG findings and diffuse or normal imaging findings could still benefit from these approaches. However, our logistic regression models revealed that new-onset seizures were associated with worse outcomes; thus, clinical decision-making should still be made on a case-by-case basis given the lack of high-quality evidence guiding therapy in these patients, as well as the documented role of therapies such as the ketogenic diet and immunotherapy ( 31 , 32 ). Some authors suggest the use of non-invasive neuromodulation techniques such as and transcranial magnetic stimulation (TMS) and electroconvulsive therapy (ECT) in the first week of SRSE, and consideration of neuromodulation techniques such as VNS, DBS and RNS after 2 weeks of therapy ( 33 ).…”
Section: Discussionmentioning
confidence: 93%
“…Although we induced KD within 48 h after admission to our PICU and restricted oral and intravenous glucose intake, a katabolic metabolism was never achieved, with ketone levels rising to a maximum of 0.7 mmoL/L. Previous authors described a similar difficulty in establishing katabolic metabolism in adolescent patients (Nabbout et al, 2023). Based on the possible role of neuroinflammation, steroids and IVIG are used in the treatment of FIRES (Kessi et al, 2020).…”
Section: Discussionmentioning
confidence: 94%